Osteogenic sarcoma - clinical cases in the practice of a children’s orthopedist and surgeon - Protsailo, M.; Dzhyvak, V.; Krycky, I.; Hoshchynskyi, P.; Gerasymets , Yu. (Journal of Education, Health and Sport, 2023)
Despite the significant achievements of modern medical science, oncological diseases pose great difficulties regarding the etiology, timely diagnosis, treatment and prevention of these ailments. Early diagnosis of tumors is the main task facing doctors. Our clinical observations over the past 5 years have shown that all children with tumors sought medical help late with advanced forms. Therefore, our task is to convey to a wide range of pediatric specialists, and not only, information that will help to recognize tumors as early as possible. Time is of crucial importance - whether the child will live or not. The given typical clinical cases should alert you to the recognition of tumors. Unfortunately, the markers of osteogenic sarcoma have not been developed at the moment, so clinical signs play an extremely important role in recognizing this disease.